Schlaganfallrehabilitation Vom Wissen zum Handeln - Tiebel, Jacob (APOLLON University Press, 2021)
Physiotherapy and occupational therapy in stroke rehabilitation has developed over the last decades into an evidence-based therapeutically science and includes forms of therapeutic treatment in which patient-oriented decisions are to be made explicitly on the basis of proven effectiveness. The starting point of this book are observations that indicate contradictions between everyday practice and the findings of the therapeutic sciences. This results in considerable difficulties in the transfer of theory to practice. The aim of this book was to present the problem from a psychological point of view, to discuss the consequences and to think about possible ways to overcome the gap between theory and practice. The current state of research on transfer of theory to practice in neurorehabilitation and the results of problem-centered interviews with experts will be presented. In summary, the results show that therapeutic behavior is influenced by a complex interaction of opportunities, capabilities and motivation. On all three levels, there are a variety of possible approaches for improvement. There are many indications that a change in behavior is possible, but that this change requires comprehensive approaches at all levels (abilities, opportunities and motivation). The results also show that appropriate actions must be tailored to the respective settings and target groups.